Single incision laparoscopic lysis of adhesions - Kasiemobi Pulliam; Gabriella Grisotti; Gregory Tiao (Elsevier, 2021)
Background: Minimally invasive approaches to surgery following open procedure are not often utilized due to known challenges of intra-operative visualization secondary to post-operative adhesions. In this case report we describe an innovative approach to the management of abdominal and thoracic post-operative adhesions via a single incision laparoscopic surgery (SILS) technique. Case Reports: Patient #1 is a 3-year-old boy with history of hepatoblastoma with pulmonary metastases status post serial thoracotomies who presented for resection of an enlarging chest wall nodule and small left upper lobe lesion. Patient #2 is a 21-year-old male with history of cerebral palsy, necrotizing enterocolitis, gastroesophageal reflux disease, with multiple prior abdominal surgeries presenting with symptomatic cholelithiasis. Results: A single incision laparoscope with insertion of various instruments through the working port was successfully utilized to aid in adhesiolysis. Patient #1 had successful resection of his thoracic lesions without requiring repeat thoracotomy. Patient #2 had partial success in lysis of adhesions but requiring conversion to open due to inadequate visualization of the gallbladder anatomy. Conclusion: The single incision laparoscopic surgical technique is a novel and valuable minimally invasive tool for lysis of adhesions in recurrent surgical procedures. There remains a low threshold to convert open for completion of the surgical procedure when there is inadequate anatomic visualization.